Manufacturing and testing of self-passivating tungsten alloys of different composition. (December 2016) - Calvo, A.; García-Rosales, C.; Koch, F.; Ordás, N.; Iturriza, I.; Greuner, H.; Pintsuk, G.; Sarbu, C.
Highlights: An ultrafine-grained W-Cr-Y alloy exhibiting Y-rich nano-precipitates was produced W-12Cr-0.5Y exhibits excellent oxidation resistance under accident-like conditions W-10Cr-2Ti2 withstands power loads of 2 MW/m 2 without damage of the bulk structure A thermal treatment at 1600°C improves thermo-shock resistance of W-10Cr-2Ti alloy Abstract: Self-passivating tungsten based alloys for the first wall armour of future fusion reactors are expected to provide a major safety advantage compared to pure tungsten in case of a loss of coolant accident with simultaneous air ingress, due to the formation of a stable protective scale at high temperatures in presence of oxygen which prevents the formation of volatile and radioactive WO3 . Bulk W-15Cr, W-10Cr-2Ti and W-12Cr-0.5Y alloys were manufactured by mechanical alloying followed by can encapsulation and HIP. This route resulted in fully dense materials with nano-structured grains. The ability of Ti and especially of Y to inhibit grain growth was observed in the W-10Cr-2Ti and W-12Cr-0.5Y alloys. Besides, Y formed Y-rich oxide nano-precipitates at the grain boundaries, and is thus expected to improve the mechanical behaviour of the Y-containing alloy. Isothermal oxidation tests at 800 ºC (1073 K) and oxidation tests under accident-like conditions revealed that the W-12Cr-0.5Y alloy exhibits the best oxidation behaviour of all alloys, especially in the accident-like scenario. Preliminary HHF tests performed at GLADIS indicated that the W-10Cr-2Ti alloy is able to withstand power densities of 2 MW/m 2 without significant damage of the bulk structure. Thermo-shock tests at JUDITH-1 to simulate mitigated disruptions resulted in chipping of part of the surface of the as-HIPed W-10Cr-2Ti alloy. An additional thermal treatment at 1600 °C (1873 K) improves the thermo-shock resistance of the W-10Cr-2Ti alloy since only crack formation is observed.